THE NATURE OF PEDAGOGICAL COMMUNICATION WITHIN THE BOUNDARIES OF SYSTEMATIC TECHNOLOGICAL TRAINING - Klinkov, G.T (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Pedagogical communication within the boundaries of technological learning is seen as an element of an effective, subject to the new educational conditions in Bulgaria methodical construction. The teacher and the pupil enter into dynamic roles, which differ significantly from the traditional training in work. The teacher is more inclined to organize the training in the alternation of different styles for communicate with the students. The students in turn are subjected to the influence of the increasingly active role of social experience Related to the work they possess from the moment of their admission to school. The importance of interpersonal communication within the boundaries of technological training in individual school degrees also changes the place and role of regulatory learning content. The inclusion of knowledge from two fundamentally different scientific fields-technology and entrepreneurship poses to the educational subjects-teacher and students the new requirement for reduction and new rubrikirane of the topics of the school, in which the effective absorption to comply with the available social experience related to the work, which the teacher forms and develops in the pupils purposefully. Related to technique and technology and secondly to their adaptability to the material and technical environment at school